FORM OF SPEECH ACTS PERLOCUSI FISH TRADERS IN THE MARKET UNDER BUKITTINGGI - Hasmi Novianti; Liga Febrina (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
The background of the Indonesian language by the Bukittinggi Fish Market has its own characteristics.Then the writer discusses the speech of fish merchant perlokusi in Bukittinggi Lower Market. The purpose of this study is to describe examples of perlocutionary speech acts made by fish sellers in the Bukittinggi Lower Market. There are 6 theoretical studies in this study, namely: 1) understanding of language, 2) understanding of pragmatics, 3) aspects of speech, 4) speech acts, 5) types of speech acts, 6) speech acts of perlokusi.This type of research is qualitative, with descriptive methods. This study uses oral data sourced from fish traders in the Bukittinggi Lower Market. This research instrument is the researcher himself using a recording device such as Type Recorder / Mobile. The equivalent method or also the information technique used in this research is a method used in techniques and techniques. In this method using power techniques sort out pragmatics. Power techniques divide pragmatics to explain the reaction of speech partners in accordance with the speech delivered by the speaker. Sources of data in this study are 21 fish marine fish commodities located in Bukittinggi Lower Market.Based on the research that has been done, the authors found 149 groups of learning perlokusi in Bukittinggi Lower Market. In this study there are several speech effects of perlokusi to persuade, attract attention, convince, and praise. The effects of perlokusi speech persuade found 33 remaining speeches. Perlokusi speech effects attract interactive attention 43 speech. The speech effect of perlocutionary faith was found in 56 utterances. Perlokusi utterance effects of choice 17 freedom of speech. From the above report it can be concluded that the perlokusi utterance effect is the easiest to use in the Lower Bukittinggi Market, namely the convincing perlokusi utterance effect of 56 utterances, and the slowest perlokusi utterance effect in the Bukittinggi lower market, namely the 17 money utterances.